2024
DOI: 10.3390/ijms25052915
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota, Tryptophan and Aryl Hydrocarbon Receptors as the Target Triad in Parkinson’s Disease—A Narrative Review

Paulina Iwaniak,
Maja Owe-Larsson,
Ewa M. Urbańska

Abstract: In the era of a steadily increasing lifespan, neurodegenerative diseases among the elderly present a significant therapeutic and socio-economic challenge. A properly balanced diet and microbiome diversity have been receiving increasing attention as targets for therapeutic interventions in neurodegeneration. Microbiota may affect cognitive function, neuronal survival and death, and gut dysbiosis was identified in Parkinson’s disease (PD). Tryptophan (Trp), an essential amino acid, is degraded by microbiota and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 190 publications
(265 reference statements)
0
1
0
Order By: Relevance
“…It is notably the case for by-products of the tryptophan/kynurenin pathway which is directly impacted by gut microbiota metabolism since several bacterial genera can produce and/or metabolize tryptophan. Widner et al reported that the severity of cognitive function impairment could be directly correlated with kynurenin/tryptophan increase [52] (for detailed information regarding this important pathway, please refer to [51,53]). Trimethylamine-n-oxide (TMAO), derived from the TMA produced by gut bacteria, has been also associated with NDDs.…”
Section: Gut Microbiota and Neurodegenerative Diseases: Crosstalk And...mentioning
confidence: 99%
“…It is notably the case for by-products of the tryptophan/kynurenin pathway which is directly impacted by gut microbiota metabolism since several bacterial genera can produce and/or metabolize tryptophan. Widner et al reported that the severity of cognitive function impairment could be directly correlated with kynurenin/tryptophan increase [52] (for detailed information regarding this important pathway, please refer to [51,53]). Trimethylamine-n-oxide (TMAO), derived from the TMA produced by gut bacteria, has been also associated with NDDs.…”
Section: Gut Microbiota and Neurodegenerative Diseases: Crosstalk And...mentioning
confidence: 99%